Conserved Karyotypes in Cophomantini: Cytogenetic Analysis of 12 Species from 3 Species Groups of Bokermannohyla (Amphibia: Anura: Hylidae) - Catroli, Glaucilene Ferreira [UNESP]; Faivovich, Julian [UNESP]; Haddad, Celio Fernando Baptista [UNESP]; Kasahara, Sanae [UNESP] (Soc Study Amphibians Reptiles, 2011)
Bokermannohyla is one of the five genera included in the recently recognized tribe Cophomantini, of the hylid frog subfamily Hylinae. Although karyotypic diversity is relatively well known in two genera of Cophomantini, Aplastodiscus and Hypsiboas, in Bokermannohyla chromosome data are restricted to only two of its 28 species. In this paper, we describe the karyotypes of 12 species of Bokermannohyla using standard staining, Ag-NOR, C-banding, DAPI, CMA(3), and BrdU incorporation. The 12 species share a similar diploid karyotype with 2n = 24 biarmed chromosomes; most observed differences involved the NOR-bearing chromosomes (and the NOR position within these chromosomes) and C-banding patterns. The overall similarity of these karyotypes with those of Aplastodiscus and Hypsiboas widens the notion of remarkable morphological homogeneity among Cophomantini karyotypes. The results obtained thus far are promising for comparative studies on the genus Bokermannohyla and, in a wider sense, will allow a better understanding of karyotype differentiation and chromosomal evolution in Cophomantini.